2017
DOI: 10.1177/1354816617729021
|View full text |Cite
|
Sign up to set email alerts
|

Educational tourism in agriculture and identity of farm successors

Abstract: Although farm visiting is gaining popularity as a type of experience-oriented tourism, the economic viability of this emerging service has not been fully established. To make it viable, it is not enough to approach educational tourism solely from a technical viewpoint, we also need to approach it from the aspect of the operator’s identity, a factor that has not been addressed fully in the arena of either rural tourism or tourism economics. Thus, by presenting a conceptual economic framework that explains the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 42 publications
0
39
0
2
Order By: Relevance
“…Furthermore, because of its importance as a basic parameter used to evaluate the performance of destination products, facilities and services (Noe and Uysal, 1997), satisfaction has been identified as the most important theme in psychology and visitor behavior. Indeed, as has been reported in other recent studies (Canavari et al, 2011;Samfira and Petroman, 2011;Park et al, 2014;European Union, 2015;Smeds et al, 2015;Johnson et al, 2016;Kowalska et al, 2016;Ohe, 2018;Sin et al, 2018), educational farms have become increasingly popular among city dwellers worldwide and many farmers have established accommodation facilities and educational farms within their businesses to create additional income, employment opportunities, educational value and cultural exchange. According to Kumbhar (2012), visitors view positively the following: convenient locations; countryside accommodation such as farmhouses, masserie (large stone farmhouses), cottages and castles; the opportunity to stay in a rural location and experience rural life; the opportunity to build relationships with local residents; experience of a clean and green environment; the tasting of good food; and the enjoyment of staying in a location with a high cultural image, with high educational value.…”
Section: Visitor Satisfaction With Farmhouses With An Educational Farm: a Conceptual Frameworkmentioning
confidence: 61%
“…Furthermore, because of its importance as a basic parameter used to evaluate the performance of destination products, facilities and services (Noe and Uysal, 1997), satisfaction has been identified as the most important theme in psychology and visitor behavior. Indeed, as has been reported in other recent studies (Canavari et al, 2011;Samfira and Petroman, 2011;Park et al, 2014;European Union, 2015;Smeds et al, 2015;Johnson et al, 2016;Kowalska et al, 2016;Ohe, 2018;Sin et al, 2018), educational farms have become increasingly popular among city dwellers worldwide and many farmers have established accommodation facilities and educational farms within their businesses to create additional income, employment opportunities, educational value and cultural exchange. According to Kumbhar (2012), visitors view positively the following: convenient locations; countryside accommodation such as farmhouses, masserie (large stone farmhouses), cottages and castles; the opportunity to stay in a rural location and experience rural life; the opportunity to build relationships with local residents; experience of a clean and green environment; the tasting of good food; and the enjoyment of staying in a location with a high cultural image, with high educational value.…”
Section: Visitor Satisfaction With Farmhouses With An Educational Farm: a Conceptual Frameworkmentioning
confidence: 61%
“…Although understudied, scholars suggest that agritourism may also serve as a way to engage consumers in ways that further contribute to sustainable LFS. Several studies have consistently shown that agritourism operators are strongly motivated to educate visitors about agricultural systems (McGehee, Kim, and Jennings 2007; Ohe 2017, 2018; Tew and Barbieri 2012). Some consumer studies, although to a lesser extent, indicated that visitors are motivated to engage in agritourism to learn about agriculture and local foods (Xu et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, in these areas, FFEFs realise important synergies among agriculture, gastronomy, territory and tourism [32][33][34][35]. Instead, from a visitor perspective, educational farms can be a place where the experiential approach [36] finds a fruitful sphere of application from the demand side [37]. However, visitors can gather experiences with plants and animals, and those which illustrate the meaning of sustainable and product-oriented production of food.…”
Section: Farmhouse Facilities With An Educational Farmmentioning
confidence: 99%